Rhetorical structure of economics Research Articles’ introductions - Somia Slaim; Hind Amel Mostari (مجلة الآداب و العلوم الإجتماعية, 2019)
Post-graduation students or researchers in different disciplines seek to write and publish research articles for graduation and academic promotion. Consequently, Studies were conducted on writing for research publication purposes; approaches as move analysis were the fruit of research in this field. Analyzing the rhetorical structure of research articles’ of different sections has attracted the attention of discourse analysists. The present study aims at investigating the move structure of the introduction section in research articles written by Algerian researchers in th field of economics. The data were collected from a corpus of 10 research articles published in 08 journals of economics in eight different Algerian universities. The analyses relied on Swales’ Model 2004 (Creating a Research Space). The findings showed that Algerian researchers are following a rhetorical move structure similar to Creating a Research Space Model of Swales (2004) in different aspects. Such results will help teaching novice researchers in writing their Research articles and getting integrated in the world of Academia.